Calprotectin — A Marker of Mortality in COPD? Results from a Prospective Cohort Study. (1st October 2013) - Holmgaard, Dennis B.; Mygind, Lone H.; Titlestad, Ingrid; Madsen, Hanne; Pedersen, Svend Stenvang; Mortensen, Ole H.; Pedersen, Court
Abstract Calprotectin comprises more than 45% of the cytosolic content of neutrophil granulocytes. Because pathogenesis, disease activity and disease progression in COPD are believed to be partly dependent of neutrophil driven inflammation we decided to investigate whether plasma level of calprotectin (p-calprotectin) was associated with all-cause mortality in patients with COPD. We measured p-calprotectin in blood samples from 460 patients with moderate to very severe COPD in stable phase. Patients were stratified into three groups according to p-calprotectin level. Outcome measure was all-cause mortality. Analyses were adjusted for factors known to influence mortality using a Cox regression analysis. We found a time dependent correlation between p-calprotectin levels and mortality during the first 5 years of follow-up. Increasing levels of p-calprotectin were associated with concomitant increases in mortality from HR 1.56 (CI 95%: 1.03 –2.38) at calprotectin between 100 –200 ng/ml to HR 2.02 (CI 95%: 1.27-3.19) at calprotectin >200 ng/ml. P-calprotectin could be a useful marker of all-cause mortality in patients suffering from moderate to very severe COPD.